2022
DOI: 10.3390/jcm11102741
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on the Effectiveness and Characteristics of Treatment Modalities for Bowen’s Disease: An Observational Study

Abstract: Treatment options for Bowen’s disease (BD) include surgical excision, cryotherapy, curettage with cautery, topical 5-fluorouracil or imiquimod, and photodynamic therapy. However, it is not clear which treatment is the most effective due to lack of studies. We reviewed the electronic medical records of 158 patients who were diagnosed with BD and treated at Seoul St. Mary’s Hospital from January 2011 to December 2020. Treatment modalities were surgical excision, cryotherapy, photodynamic therapy, and imiquimod. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…A previous study showed that PDT is a relatively effective treatment modality for BD, the overall clearance rate was 63.40% ( 21 ). An observational study compared different therapies: cryotherapy with the longest average treatment period, followed by imiquimod, PDT, and excision; surgical excision with the highest and PDT with the lowest therapeutic efficacy; imiquimod with recurrence rate was the highest ( 22 ). The efficacy of PDT in the treatment of BD varies among different studies, a meta-analysis shows that PDT treats BD with better efficacy, less recurrence, and better cosmetic outcomes than cryotherapy and 5-FU ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study showed that PDT is a relatively effective treatment modality for BD, the overall clearance rate was 63.40% ( 21 ). An observational study compared different therapies: cryotherapy with the longest average treatment period, followed by imiquimod, PDT, and excision; surgical excision with the highest and PDT with the lowest therapeutic efficacy; imiquimod with recurrence rate was the highest ( 22 ). The efficacy of PDT in the treatment of BD varies among different studies, a meta-analysis shows that PDT treats BD with better efficacy, less recurrence, and better cosmetic outcomes than cryotherapy and 5-FU ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Общая медианная доза облучения составила 50 Гр (диапазон 25-66 Гр). Все очаги поражения были локально контролируемыми, с медианой наблюдения 25 месяцев, только с легкой или умеренной эритемой, десквамацией и острым отеком после лучевой терапии, которые разрешились в течение 1 месяца [40]. Местная химиотерапия очагов поражения при болезни Боуэна включает в себя наружное применение лекарственных средств.…”
Section: обзор литературыunclassified
“…При болезни Боуэна также была отм ечена эффективность при использовании этого препарата дважды в день в течение 80-90 дней. Лечение переносится хорошо с появлением легкого воспаления через 6 недель применения и с незначительными побочными эффектами (зуд и сухость) [40]. Также имеется сообщение об успешном применении геля, содержащего ингенол мебутат, для лечения очагов болезни Боуэна небольших размеров [46].…”
Section: обзор литературыunclassified
“…Infection caused by human papillomavirus (HPV) on the skin is a key risk factor for Bowen's disease development. [ 3 ] HPV is a class of exceeding 150 similar viruses, some can bring about cancer. HPV 18, 16, 48, and 34, can cause Bowen's disease at the genital site.…”
Section: Introductionmentioning
confidence: 99%